2019
DOI: 10.1038/s41598-019-55085-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of neural perceptual vowel spaces during the first year of life

Abstract: This study measured infants’ neural responses for spectral changes between all pairs of a set of English vowels. In contrast to previous methods that only allow for the assessment of a few phonetic contrasts, we present a new method that allows us to assess changes in spectral sensitivity across the entire vowel space and create two-dimensional perceptual maps of the infants’ vowel development. Infants aged four to eleven months were played long series of concatenated vowels, and the neural response to each vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The PCM model, in addition, proposes that, during development, infants can use both an acoustically grounded perception mode and categorical perception in parallel (Gallé & McMurray, 2014, based on Pisoni & Tash, 1974). Infants would co‐improve both modes constantly with age, but younger infants would rely more on the acoustic channel than older infants (see McCarthy et al, 2019, for spectral vowel properties, and the discussion in Mugitani et al, 2009, for vowel length properties).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCM model, in addition, proposes that, during development, infants can use both an acoustically grounded perception mode and categorical perception in parallel (Gallé & McMurray, 2014, based on Pisoni & Tash, 1974). Infants would co‐improve both modes constantly with age, but younger infants would rely more on the acoustic channel than older infants (see McCarthy et al, 2019, for spectral vowel properties, and the discussion in Mugitani et al, 2009, for vowel length properties).…”
Section: Discussionmentioning
confidence: 99%
“…According to PRIMIR, infants' earliest speech perception is organized on a general perceptual level. Phonetic information is encoded following primary auditory processing mechanisms (McCarthy et al, 2019) and modulated by initial biases (e.g., preference for ID‐speech, point vowels, a.o.). With growing language experience, these early sound representations are reorganized as a function of the frequency and distribution of features (including acoustic, auditory–visual, and articulatory information) encountered in the environment, and as a function of contextual needs (e.g., word learning).…”
mentioning
confidence: 99%
“…Neural commitment to the native language at the age of 7.5 months can predict language development up to two years following initial neural measurements (Rivera-Gaxiola, Klarman, et al 2005;Rivera-Gaxiola, Silva-Pereyra, et al 2005;Kuhl et al 2008). A recent study of acoustic change complex in the infant LLR demonstrated a transformation from a merely acoustical-driven pattern to native phonemecategory sensitivity around the age of 6 months (McCarthy et al 2019). Though the findings from these pioneering LLR-based (mostly MMN) studies provide an initial neural explanation for perceptual narrowing, these studies are focused largely on the role of the cortex.…”
Section: Introductionmentioning
confidence: 98%
“…On a related note, early auditory‐based discrimination was reported in a recent neurophysiological study of infants learning British English by McCarthy, Skoruppa, and Iverson (2019). McCarthy et al.…”
Section: The Age Of the Universal Listenermentioning
confidence: 68%